2011
DOI: 10.4018/jmcmc.2011070101
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Backoff Algorithm for Mobile Ad-Hoc Networks

Abstract: Collision is a common problem in Mobile Ad Hoc Networks (MANETs). There are several backoff algorithms that have been proposed to avoid this problem. This paper proposes a new backoff algorithm called the Square Root Backoff (SRB). Moreover, it identifies that no algorithm can perform the best in all cases. Therefore, an adaptive strategy is proposed to choose the best backoff mechanism from a set of mechanisms based on network density and mobility parameters. The proposed adaptive algorithm is implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, it requires more computational resources and takes more time. In (Khamayseh et al, 2011), the authors suggested a system in which a trust table is used to store the trusted nodes. In their system, the RREP in the routing protocol is overloaded with the trusted value of the replying node.…”
Section: • Grey-hole Attackmentioning
confidence: 99%
“…However, it requires more computational resources and takes more time. In (Khamayseh et al, 2011), the authors suggested a system in which a trust table is used to store the trusted nodes. In their system, the RREP in the routing protocol is overloaded with the trusted value of the replying node.…”
Section: • Grey-hole Attackmentioning
confidence: 99%
“…Khamayseh, Y., et al, (2011) [6] proposed a solution for a blackhole attack using a new protocol. However, they only showed a modification of the AODV protocol.…”
Section: A Specific Solutions For Blackhole Attacksmentioning
confidence: 99%